Role of Chondroitin Sulfation Following Spinal Cord Injury - Hussein, Rowan K.; Mencio, Caitlin P.; Katagiri, Yasuhiro; Brake, Alexis M.; Geller, Herbert M. (Frontiers in Cellular Neuroscience, 2020)
Traumatic spinal cord injury produces long-term neurological damage, and presents a significant public health problem with nearly 18,000 new cases per year in the U.S. The injury results in both acute and chronic changes in the spinal cord, ultimately resulting in the production of a glial scar, consisting of multiple cells including fibroblasts, macrophages, microglia, and reactive astrocytes. Within the scar, there is an accumulation of extracellular matrix molecules – primarily tenascins and Chondroitin sulfate proteoglycans (CSPGs)– which are considered to be inhibitory to axonal regeneration. In this review we discuss the role of CSPGs in the injury response, especially how sulfated glysosaminoglycan (GAG) chains act to inhibit plasticity and regeneration. This includes how sulfation of GAG chains influences their biological activity and interactions with potential receptors. Comprehending the role of CSPGs in the inhibitory properties of the glial scar provides critical knowledge in the much needed production of new therapies.